Chili and Eggplant Seeds: what are the benefits and influence of Planting Horticultural Crops on the Inflation Rate of Munggu Village? - Handayani, Safitri Windi; Nisa, Miftah Khairun; Susanti, Elinda; Nur, Ami Yani; Abbas, Sayid (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
Horticulture as it relates to the cultivation of garden vegetation. In a broader sense, the term pertains to the modern cultivation of garden plants. Horticultural products can be cultivated on a modest scale, such as in a household. By disseminating horticultural seeds, the researchers hope to reduce the market price of chilies or prevent inflation, particularly in Munggu Village, Bungkal District, Ponorogo Regency. The researcher conducted a direct survey in Munggu Village, Bungkal District, Ponorogo Regency, as part of the observational research method. Researchers' surveys revealed that the majority of Munggu Village residents were cultivators. As a result, the service's work program involves the distribution of horticultural seedlings in the form of chili plants and eggplant plants to every resident of Munggu Village. The current inflation is heavily influenced by rising food prices, which have a significant impact on rising food prices on the market. The distribution of horticultural seedlings, such as chili and eggplant, has the potential to reduce inflation. Low and consistent inflation is a precondition for sustained economic growth, which ultimately contributes to the improvement of people's standard of living. The significance of controlling inflation stems from the fact that high and unstable inflation is detrimental to society's socioeconomic conditions.